Prevalence and factors associated with overweight and obesity among secondary school student in Puchong, Selangor, Malaysia - Queen, Ojo Esehi (2018)
Background: Worldwide, overweight and obesity are one among the major public health problem which is resposibles for 5% of death yearly. World Health Organization (WHO) reported that there is an increase in the prevalence of overweight and obesity; about 1.9 billion adults were overweight and 600 million were obese, 18% of children and adolescents aged 5-19 were either overweight or obese in 2016. The rate of obesity has tripled, as they rapidly become more urbanized with increased consumption of calorie foods and adoption of a more sedentary life-style. In Malaysia over the past three decade, there has been a clear increase in the prevalence of overweight and obesity. Among secondary school children, 44% were perceived overweight while 14% obesity (Adolescent Nutrition Survey, NHMS, 2017). Objectives: The objective of the study is to determine the prevalence and factors associated with overweight and obesity among secondary school student in Puchong district, Selangor Malaysia. Methodology: A cross-sectional study was conducted in secondary schools in Puchong district of Selangor Malaysia. A constructed validated pretested questionnaire was used for the data collection. The questionnaire consists of six sections, which include: a) Socio-Demography charateristics, b) Physical Activity Questionnaire c) Self Esteem Scale, d) Body Parts Satisfaction Scale e) Body Size Perception Scale and e) Smoking questionnaire. Weight and height was measured and converted to body mass index (BMI). The study analysis was done using Statistical Package for social sciences (SPSS) version 22. Basic descriptive analysis was carried out for the mean, median, frequency and percentage. Chi square test was used to test association between the variables. Simple logistic regression was used to determine the crude odd ratio and variables with p value < 0.25 were entered into the multiple logistic regression to determine the adjusted odd ratio/predictors of overweight and obesity. Level of significance was set at 0.05. Result: The response rate was 100%. The prevalence of overweight and obesity was 10% and 3.9% respectively. Out of the 281 student that participated in the study 164 were female (58.4%) while 117 were male (41.6%). Age (0.001), father’s education (p=0.006), mother education (p= 0.023), body part satisfaction (p= 0.001) and body image (p= 0.009) were significantly associated with overweight and obesity, then were entered into logistic regression model. Multiple logistic regression analysis showed that the predictors of obesity were age (AOR=2.756, 95% CI: 1.327-5.721, p=0.007) body parts satisfaction (AOR=4.019, 95% CI: 1.925-8.390, p= 0.001) and body size perception (AOR=2.917, 95% CI: 1.204-7.202, p= 0.018). Conclusion: In conclusion the significant predictor of overweight and obesity among secondary school student in Puchong district Selangor, Malaysia were age, body parts satisfaction and body size perception. The findings from this study can be used by policy makers to conduct a more represatitive study and plan preventive measures to tackle the increasing prevalence of overweight and obesity among the target population.